Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

If [tex]\( f(x) = 3x^2 + 1 \)[/tex] and [tex]\( g(x) = 1 - x \)[/tex], what is the value of [tex]\( (f - g)(2) \)[/tex]?

A. 12
B. 14
C. 36
D. 38


Sagot :

To find the value of [tex]\((f - g)(2)\)[/tex], let's break it down step-by-step.

### Step 1: Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 2 \)[/tex]

The function [tex]\( f(x) \)[/tex] is given by:
[tex]\[ f(x) = 3x^2 + 1 \][/tex]

Substitute [tex]\( x = 2 \)[/tex] into the function:
[tex]\[ f(2) = 3(2)^2 + 1 \][/tex]
[tex]\[ f(2) = 3(4) + 1 \][/tex]
[tex]\[ f(2) = 12 + 1 \][/tex]
[tex]\[ f(2) = 13 \][/tex]

### Step 2: Evaluate [tex]\( g(x) \)[/tex] at [tex]\( x = 2 \)[/tex]

The function [tex]\( g(x) \)[/tex] is given by:
[tex]\[ g(x) = 1 - x \][/tex]

Substitute [tex]\( x = 2 \)[/tex] into the function:
[tex]\[ g(2) = 1 - 2 \][/tex]
[tex]\[ g(2) = -1 \][/tex]

### Step 3: Calculate [tex]\((f - g)(2)\)[/tex]

Now, we need to find [tex]\((f - g)(2)\)[/tex], which means:
[tex]\[ (f - g)(2) = f(2) - g(2) \][/tex]

Using the values we found:
[tex]\[ (f - g)(2) = 13 - (-1) \][/tex]
[tex]\[ (f - g)(2) = 13 + 1 \][/tex]
[tex]\[ (f - g)(2) = 14 \][/tex]

Therefore, the value of [tex]\((f - g)(2)\)[/tex] is [tex]\( \boxed{14} \)[/tex].